A stable, novel catalyst improves hydrogen production in a membrane reactor - Irusta, S. (2005)
The dry reforming of methane as a source of H2 was performed using a well-known catalyst, Rh/La2O3, together with a novel one, Rh/La2O3-SiO2, in a hydrogen-permeable membrane reactor. The catalysts were characterized by XRD, TPR, FTIR, H2 and CO chemisorption. In all lanthanum-based catalysts, the activity remained constant after 100 h on stream at 823 K. The basis of their high stability could be traced back to the strong metal-support interaction (TPR) in Rh/La2O3 catalysts. The La 2O3-SiO2 solids are also stable even though a weaker rhodium-lanthanum interaction (TPR) can be observed. The incorporation of the promoter (La2O3) to the silica support induces a parallel increase in the metal dispersion (CO adsorption). The effect of the operation variables upon the performance of the membrane reactor was also studied. The novel Rh (0.6%)/La2O3 (27%)-SiO2 catalyst proved to be the best formulation. Operating the membrane reactor at 823 K, both methane and CO2 conversions were 40% higher than the equilibrium values, producing 0.5 mol H2/mol CH4. This catalyst, tested at W/F three times lower than Rh (0.6%)/La2O 3, showed a similar performance. Both the increase of the sweep gas flow rate and the decrease of the permeation area significantly affected methane conversion and H2 production. The presence of tiny amounts of graphite only detectable through LRS did not endanger membrane stability. The better performance of Rh (0.6%)/La2O3 (27%)-SiO 2 is related to the high dispersion.